KEKUATAN SURAT PELEPASAN TANAH ADAT TERHADAP SERTIFIKAT TANAH YANG DITERBITKAN - Andi Annisa Nurlia Mamonto (UNES Law Review, 2023)
For the traditional law society, land has a very important position. Together with the influences of regulations outside of the traditional law community, therefore, there is a change of value standard of the utilization of rights upon traditional land by the traditional law society itself. Land not only has social values; however, it also has economic values, which means, the rights of ownership of traditional land now can be transferred by the traditional authority to other parties outside of the traditional law society by the release of rights upon traditional land, it can be concluded that the ownership of disputed land by the government without a letter of customary waiver from customary parties is an act against local customary law, which has been supported by valid evidence in accordance with the decisions of the district court and high court, therefore the Land Agency must be more thorough in issue land certificates so that they can protect land rights, especially over customary land rights, for owners who have a weak position.